Protective effects of curcumin against osteoporosis and its molecular mechanisms: a recent review in preclinical trials - Yang, Shenglei; Sun, Yuying; Kapilevich, Leonid; Zhang, Xin’an; Huang, Yue (Frontiers in Pharmacology, 2023)
Osteoporosis (OP) is one of the most common metabolic skeletal disorders and is commonly seen in the elderly population and postmenopausal women. It is mainly associated with progressive loss of bone mineral density, persistent deterioration of bone microarchitecture, and increased fracture risk. To date, drug therapy is the primary method used to prevent and treat OP. However, long-term drug therapy inevitably leads to drug resistance and specific side effects. Therefore, researchers are constantly searching for new monomer compounds from natural plants. As a candidate for the treatment of OP, curcumin (CUR) is a natural phenolic compound with various pharmacological and biological activities, including antioxidant, anti-apoptotic, and anti-inflammatory. This compound has gained research attention for maintaining bone health in various OP models. We reviewed preclinical and clinical studies of CUR in preventing and alleviating OP. These results suggest that if subjected to rigorous pharmacological and clinical trials, naturally-derived CUR could be used as a complementary and alternative medicine for the treatment of OP by targeting osteoporosis-related mechanistic pathways. This review summarizes the mechanisms of action and potential therapeutic applications of CUR in the prevention and mitigation of OP and provides reference for further research and development of CUR.